Europa / Amerika : Die Geschichte einer künstlerischen Faszination seit 1940. (Köln : Museum Ludwig, 1986)
Baumgarten, Lothar ; Fabro, Luciano ; Gilbert & George ; Immendorff, Jörg ; Kiecol, Hubert ; Kounellis, Jannis ; Leroy, Eugene ; Lüpertz, Markus ; Manzoni, Piero ; Merz, Mario ; Oehlen, Markus ; Penck, A.R. ; Résuichot, Bernard ; Toroni, Niele ; Avery, Milton ; Brecht, George ; Dine, Jim ; Fisher, Joel ; Gorky, Arshile ; Halley, Peter ; Holzer, Jenny ; Judd, Don ; Kiesler, Friedrich ; Koons, Jeff ; Levine, Sherrie ; de Maria, Walter ; Morley, Malcolm ; Newman, Barnett ; Rauschenberg, Robert ; Rothko, Mark ; Salle, David ; Samaras, Lucas ; Schnabel, Julian ; Thiebaud, Wayne ; etc.
Europa / Amerika : Die Geschichte einer künstlerischen Faszination seit 1940, Museum Ludwig, Köln, 6. September - 30. November 1986
boek
Keywords: Europa; Amerika